Do Banks Issue Equity When They Are Poorly Capitalized? - Dinger, Valeriya; Vallascas, Francesco (Journal of Financial and Quantitative Analysis, 2016)
Debt overhang and moral hazard predict that poorly capitalized banks have a lower likelihood to issue equity, while the presence of regulatory and market pressures posits an opposite theoretical prediction. By using an international sample of bank seasoned equity offerings (SEOs), we show that the likelihood of issuing SEOs is higher in poorly capitalized banks and that such banks prefer SEOs to alternative capitalization strategies. A series of tests exploring the variation of capital regulation and market discipline show that market mechanisms rather than capital regulation are the primary driver of the decision to issue by poorly capitalized banks.